Comparative analysis of fuel cell and battery energy systems for Internet of Things devices. (November 2020) - Akimoto, Yutaro; Takezawa, Hinato; Iijima, Yosuke; Suzuki, Shin-nosuke; Okajima, Keiichi
Abstract: Most Internet of Things (IoT) devices are powered by electrical grids. Therefore, the supply of power to these devices is interrupted by critical grid failures, which can occur during natural disasters. To support the development of IoT devices that can operate during disasters, the most commonly used energy systems were evaluated. In this study, lithium-ion batteries and fuel cells were compared to evaluate and compare their operation time, output power, and general technical specifications. The operating time of the fuel cell 10W was 57 min because of the failure, which was shorter than the other systems. Moreover, an IoT device using Raspberry Pi was evaluated to determine the optimal energy system. Currently, batteries are more cost-effective, however as the cost of fuel cells comes down, the higher power density will be valuable.